Unique Dispersal of the Changjiang-Diluted Water Plume in the East China Sea Revealed from Satellite Monitoring of Colored Dissolved Organic Matter (CDOM) - Hiroaki Sasaki; Yasushi Gomi; Takamasa Asai; Masashi Shibata; Yoko Kiyomoto; Kazumaro Okamura; Kou Nishiuchi; Toru Hasegawa; Haruya Yamada (Terrestrial, Atmospheric and Oceanic Sciences, 2014)

(untitled)
The optical properties of colored dissolved organic matter (CDOM) in the Changjiang (Yangtze River) plume water were investigated during the summer of 2009 and 2010. The absorption coefficient of CDOM at 325 nm (aCDOM) increased inversely with decreasing sea-surface salinity (SSS), implying that aCDOM can be used as a natural tracer of Changjiang-diluted water (CDW). This aCDOM vs. SSS relationship, however, differed between 2009 and 2010. For mapping the CDW plume, the aCDOM was retrieved from an ocean-color satellite. Values of SSS were also derived from the satellite-retrieved aCDOM using field-based SSS vs. aCDOM relationships. Satellite observations revealed the temporary variable eastward extension of a high aCDOM, low SSS CDW plume in the central East China Sea (ECS) during the summer. The CDW plume during the summer of 2010 extended southeastward from the mouth of the Changjiang (Yangtze River) to almost 26°N. Moreover, the branch of this southeastward CDW plume was seen to extend northeastward to the eastern ECS where the Kuroshio Current flows northeastward along the shelf break. Subsequently, this branch was distributed around southern Kyushu. Satellite observations revealed this unique dispersal of the CDW plume, which illustrates that the aCDOM and SSS from ocean-color satellite data are useful for monitoring the dispersal of this river-water plume.